Cytogenetic and molecular characteristics of rye genome in octoploid triticale (× Triticosecale Wittmack) - Evtushenko, Elena V. (Comp Cytogenet, 2019)
Abstract. Alloploidization resulting from remote (interspecific or intergeneric) hybridization is one of the main factors in plant evolution, leading to the formation of new species. Triticale (× Triticosecale Wittmack, 1889) is the first artificial species created by crossing wheat (Triticum spp.) and rye (Secale cereale Linnaeus, 1753) and has a great potential as a grain and forage crop. Remote hybridization is a stress factor that causes a rapid reorganization of the parental genomes in hybrid progeny (“genomic shock”) and is accompanied by abnormalities in the chromosome set of hybrids. The formation of the hybrid genome and its subsequent stabilization are directly related to the normalization of meiosis and the correct chromosome segregation. The aim of this work was to cytogenetically characterize triticale (× Triticosecale rimpaui Wittmack, 1899, AABBDDRR) obtained by crossing Triticum aestivum Linnaeus, 1753. Triple Dirk D × Secale cereale L. Korotkostebel’naya 69 in F(3)–F(6) generations of hybrids, and to trace the process of genetic stabilization of hybrid genomes. Also, a comparative analysis of the nucleotide sequences of the centromeric histone CENH3 genes was performed in wheat-rye allopolyploids of various ploidy as well as their parental forms. In the hybrid genomes of octoploid triticale an increased expression of the rye CENH3 variants was detected. The octoploid triticale plants contain complete chromosome sets of the parental subgenomes maintaining the chromosome balance and meiotic stability. For three generations the percentage of aneuploids in the progeny of such plants has been gradually decreasing, and they maintain a complete set of the paternal rye chromosomes. However, the emergence of hexaploid and new aneuploid plants in F(5) and F(6) generations indicates that stabilization of the hybrid genome is not complete yet. This conclusion was confirmed by the analysis of morphological features in hybrid plants: the progeny of one plant having the whole chromosome sets of parental subgenomes showed significant morphological variations in awn length and spike density. Thus, we expect that the results of our karyotyping of octoploid triticales obtained by crossing hexaploid wheat to diploid rye supplemented by comparative analysis of CENH3 sequences will be applicable to targeted breeding of stable octo- and hexaploid hybrids.